Social Return on Investment of Gastronomy Tourism in Chanthaburi Province - Preepremmote, Patcharee; Charoenphun, Narin; Phukseng, Thanaphon; Cheawchan, Kanyarat; Singhapreecha, Charuk; Tengsuwan, Parichat; Yuvanatemiya, Vasin (Journal of Applied Economics and Management Strategy, 2025)
This study aims to develop an outcome mapping of a food tourism project in Chanthaburi Province and assess its social impact. Using both ex-ante and ongoing evaluation approaches, the research incorporates focus group discussions and in-depth interviews with 91 stakeholders, alongside questionnaires completed by 900 participants and other affected individuals. The analysis covers the project's activities, outputs, outcomes, and both tangible and intangible impacts-whether intended or unintended. The findings indicate that the project contributed to: (1) sustainable income generation for farmers, restaurant operators, and food entrepreneurs; (2) the promotion of safe and environmentally friendly agricultural practices; (3) improvements in community well-being; (4) expansion of tourism, particularly food tourism; and (5) establishment of partnerships and cooperative networks for local development. A social impact assessment conducted for the period 2023–2027, applying a discount rate of 3.5%, estimates a net present value of 274,533,440 Thai Baht (THB) and a social return on investment (SROI) ratio of 6.81. These results suggest that the project yields substantial benefits that outweigh its costs, making it a valuable and sustainable investment.